Hubungan Dukungan Keluarga dengan Kelengkapan Imunisasi Dasar Balita di Desa Mumbulsari - Yuni Handayani (Puslitbang Sinergis Asa Professional, 2021)
Immunization has proven to be one of the most important public health efforts. Immunization programs shown remarkable success funds are a very cost-effective effort in preventing infectious diseases. Immunization is influenced by several factors, including knowledge level, mother’s age, education level, occupation, number of children and family support. This aims to analyze the Relationship of Family Support with the completeness of Basic Immunization Balita in Village Mumbulsari of Sub-districts Mumbulsari - Jember. In 2015, East Java accounted for the largest diphtheria cases (63%) and has not met the target of SPM (Minimum Service Standards). According to the health profile of jember district 2014 Of 49 health centers, there are 4 other health centers that have not reached the target of UCI are Kalisat health center (92%), Pakusari (86%), Bangsalsari (86%) and Mumbulsari (75%). This research design use correctional with Cross Sectional approach.Population 90 mothers who have children under the age of two years.After slovin formula obtained 73 respondents as sample by using simple random sampling technique. The result showed Basic Immunization of complete 53 (73%) and Basic Immunization of incomplete 20(27%), good family support 58(79,5%), less family support 15 (20,5%). Data analysis test using Spearman Rank with p-value 0,000 <α 0,05 which means there is a Family Support Relationship with Basic Immunization Equipment Balita. It is recommended that the next community who have a child under two years give family good support to basic immunization for granting mothers complete.